Biochar effects on crop yields with and without fertilizer: A meta‐analysis of field studies using separate controls. (10th December 2019) - Ye, Lili; Camps‐Arbestain, Marta; Shen, Qinhua; Lehmann, Johannes; Singh, Balwant; Sabir, Muhammad
Abstract: The added value of biochar when applied along with fertilizers, beyond that of the fertilizers themselves, has not been summarized. Focusing on direct comparisons between biochar additions (≤20 t ha −1 ) – separately considering the addition or not of inorganic fertilizers (IF) and/or organic amendments (OA) along with biochar – and two different controls (with and without the addition of IF and/or OA), we carried out a meta‐analysis to explain short‐term (1‐year) field responses in crop yield across different climates, soils, biochars and management practices worldwide. Compared with the non‐fertilized control, a 26% (CI: 15%–40%) increase in yield was observed with the use of IF only, whereas that of biochar along with IF caused a 48% (CI: 30%–70%) increase. Compared with the use of IF only, the addition of biochar along with IF caused a 15% (CI: 11%–19%) increase in yield, indicating that biochar was as effective as fertilizers in increasing crop yields when added in combination. The use of biochar alone did not increase crop yield regardless of the control considered. Whereas in the short term, liming may have partly contributed to the beneficial effect of biochar (>90% was plant‐derived) when added along with IF, a separate meta‐analysis – using those studies that reported crop yields for different years after a single biochar application – showed a 31% (CI: 17%–49%) increase in crop yield over time (≥ 3 years), which denotes the influence of biochar properties other than liming (i.e. an increase in CEC). Our results also suggest that biochar application rates > 10 t ha −1 do not contribute to greater crop yield (at least in the short term). Data limitations precluded identification of the influence of feedstock, production conditions or climatic conditions without bias. As the response of crop yield to biochar addition was less a result of climatic zones or soil type than fertilizer use (chiefly N additions), the choice of nutrient addition along with biochar should be priorities for future research and development regardless of the region.